Case report: Pulmonary arterial hypertension in ENG-related hereditary hemorrhagic telangiectasia - Liu, Dong; Xu, Feiya; Gao, Qian; Zhai, Zhenguo (Frontiers in Cardiovascular Medicine, 2022)
A young adult woman presented with exertional dyspnea and she had had recurrent epistaxis for more than 10 years. On physical examination, cyanosis was noted on the lips, and telangiectasias were seen on the oral mucosa and fingertips. Routine investigations revealed iron deficiency anemia and slightly elevated bilirubin. The result of right heart catheterization was indicative of pulmonary arterial hypertension (PAH). Pulmonary angiography showed arteriovenous malformations of the left upper pulmonary artery, and anterior cerebral artery malformation was seen in cranial computed tomographic angiogram. Genetic testing revealed that she and her three daughters carried heterozygous variant of ENG c.1195-1196del p.Arg399GlyfsTer2, which is characterized by pulmonary and cerebral arteriovenous malformations. In addition, our patient had pulmonary hypertension (PH) that is commonly associated with ACVRL1 mutations, revealing her phenotype was not consistent with isolated ENG genetic mutations. Here, we report a case with hereditary hemorrhagic telangiectasia (HHT) combined with PAH, which is associated with interesting differential diagnosis and etiological analysis. We have discussed the relationship between PH and HHT and the characteristics of PAH in HHT patients.